Cardiac MR elastography for quantitative assessment of elevated myocardial stiffness in cardiac amyloidosis. Issue 5 (25th February 2017) - Arani, Arvin; Arunachalam, Shivaram P.; Chang, Ian C.Y.; Baffour, Francis; Rossman, Phillip J.; Glaser, Kevin J.; Trzasko, Joshua D.; McGee, Kiaran P.; Manduca, Armando; Grogan, Martha; Dispenzieri, Angela; Ehman, Richard L.; et al.
Abstract : Purpose: To evaluate if cardiac magnetic resonance elastography (MRE) can measure increased stiffness in patients with cardiac amyloidosis. Myocardial tissue stiffness plays an important role in cardiac function. A noninvasive quantitative imaging technique capable of measuring myocardial stiffness could aid in disease diagnosis, therapy monitoring, and disease prognostic strategies. We recently developed a high‐frequency cardiac MRE technique capable of making noninvasive stiffness measurements. Materials and Methods: In all, 16 volunteers and 22 patients with cardiac amyloidosis were enrolled in this study after Institutional Review Board approval and obtaining formal written consent. All subjects were imaged head‐first in the supine position in a 1.5T closed‐bore MR imager. 3D MRE was performed using 5 mm isotropic resolution oblique short‐axis slices and a vibration frequency of 140 Hz to obtain global quantitative in vivo left ventricular stiffness measurements. The median stiffness was compared between the two cohorts. An octahedral shear strain signal‐to‐noise ratio (OSS‐SNR) threshold of 1.17 was used to exclude exams with insufficient motion amplitude. Results: Five volunteers and six patients had to be excluded from the study because they fell below the 1.17 OSS‐SNR threshold. The myocardial stiffness of cardiac amyloid patients (median: 11.4 kPa, min: 9.2, max: 15.7) was significantly higher ( P = 0.0008) than normal controls (median: 8.2 kPa, min: 7.2, max: 11.8). Conclusion: This study demonstrates the feasibility of 3D high‐frequency cardiac MRE as a contrast‐agent‐free diagnostic imaging technique for cardiac amyloidosis. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1361–1367.